Stable expression and characterization of a fungal pectinase and bacterial peroxidase genes in tobacco chloroplast - Espinoza Sánchez, Edward Alexander; Alvarez Hernández, Marianela Hazel; Torres Castillo, Jorge Ariel; Rascón Cruz, Quintín; Gutiérrez Díez, Adriana; Zavala García, Francisco; Sinagawa García, Sugey Ramona (2015)
The high capacity of chloroplast genome response to integrate and express transgenes at high levels makes this technology a good option to produce proteins of interest. This report presents the stable expression of Pectin lyase (PelA gene) and the first stable expression of manganese peroxidase (MnP-2 gene) from the chloroplast genome. Results: pES4 and pES5 vectors were derived from pPV111A plasmid and contain the PelA and MnP-2 synthetic genes, respectively. Both genes are flanked by a synthetic rrn16S promoter and the 3′UTR from rbcL gene. Efficient gene integration into both inverted repeats of the intergenic region between rrn16S and 3′rps′12 was confirmed by Southern blot. Stable processing and expression of the RNA were confirmed by Northern blot analysis. Enzymatic activity was evaluated to detect expression and functionality of both enzymes. In general, mature plants showed more activity than young transplastomic plants. Compared to wild type plants, transplastomic events expressing pectin lyase exhibited enzymatic activity above 58.5% of total soluble protein at neutral pH and 60°C. In contrast, MnP-2 showed high activity at pH 6 with optimum temperature at 65°C. Neither transplastomic plant exhibited an abnormal phenotype. Conclusion: This study demonstrated that hydrolytic genes PelA and MnP-2 could be integrated and expressed correctly from the chloroplast genome of tobacco plants. A whole plant, having ~470 g of biomass could feasibly yield 66,676.25 units of pectin or 21,715.46 units of manganese peroxidase. Also, this study provides new information about methods and strategies for the expression of enzymes with industrial value.